The role of social mechanisms of change in women's addiction recovery trajectories. (3rd September 2021) - Collinson, Beth; Hall, Lauren
Abstract: Recovery from substance use addiction is a socially mediated process, with the formation of pro-social networks and engagement in community resources acting as catalysts for growth and change. Gender is a key mediator in pathways into and out of substance use, however literature that considers gender dimensions within the recovery paradigm is limited. This paper presents a secondary analysis of two qualitative studies undertaken with nine women in recovery—recruited based on their engagement with community support services. Thematic analysis of the women's narratives elucidates the role of social mechanisms in the recovery processes of women who are accessing community support, in order to inform progressive policy change that better acknowledges, understands and enhances women's experience of recovery. Based on the emergent themes of trauma; intimate relationships; social networks; and identity, we consider practical implications for community based recovery support.